2008
DOI: 10.1152/jn.00883.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TRPA1 Agonists Mustard Oil and Cinnamaldehyde on Lumbar Spinal Wide-Dynamic Range Neuronal Responses to Innocuous and Noxious Cutaneous Stimuli in Rats

Abstract: Effects of TRPA1 agonists mustard oil and cinnamaldehyde on lumbar spinal wide-dynamic range neuronal responses to innocuous and noxious cutaneous stimuli in rats. J Neurophysiol 99: 415-425, 2008. First published October 17, 2007 doi:10.1152/jn.00883.2007. Mustard oil [allyl isothiocyanate (AITC)] and cinnamaldehyde (CA), agonists of the ion channel TRPA1 expressed in sensory neurons, elicit a burning sensation and heat hyperalgesia. We tested whether these phenomena are reflected in the responses of lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
10
42
0
Order By: Relevance
“…Consistent with prior observations (Carstens 1997;Merrill et al 2008), the majority of the present WDR neurons responded to thermal stimuli and the irritant chemicals AITC and capsaicin, in addition to IBA. No IBA-responsive neurons were found that did not additionally respond to AITC and/or capsaicin, which induce burning pain, suggesting that "tingle-specific" neurons are rare or nonexistent.…”
Section: Wdr Neurons and Tinglesupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with prior observations (Carstens 1997;Merrill et al 2008), the majority of the present WDR neurons responded to thermal stimuli and the irritant chemicals AITC and capsaicin, in addition to IBA. No IBA-responsive neurons were found that did not additionally respond to AITC and/or capsaicin, which induce burning pain, suggesting that "tingle-specific" neurons are rare or nonexistent.…”
Section: Wdr Neurons and Tinglesupporting
confidence: 91%
“…The spinous processes of L1 and T13 were removed and the transverse processes of L2 and T12 were clamped for stability (for details, see Merrill et al 2008). After exposure of the spinal cord Address for reprint requests and other correspondence: E. Carstens,…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, these findings could be evidence of an interaction between TRPA1 and TRPV channels. AITC can cause sensitization of responses to heat (Martin et al, 2004;Simons et al, 2004;Carstens and Mitsuyo, 2005;Merrill et al, 2008;Sawyer et al, 2009) and this is thought to be the result of TRPA1-mediated sensitization of TRPV1 (Jansen et al, 1978). Because HC030031 may operate as an allosteric modulator (Xiao et al, 2008), it is possible that this antagonist elicits a conformational change in TRPA1 that, while antagonizing channel function, is able to activate the biochemical pathways responsible for TRPV sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…7,8). Specifically, TRPA1 is exclusively activated by mustard oil, cinnamaldehyde (a compound found in cinnamon), lipids (9), chlorine (see below), the pollutant acrolein (10)(11)(12)(13)(14), as well as endogenous aldehydes (15). TRPA1 is not inhibited by capsazepine but rather by a specific antagonist, HC-030031 (6).…”
Section: Trpa1 and Cigarette Smokementioning
confidence: 99%